UPAYA PENINGKATKAN NILAI JUAL PRODUK RENGGINANG DESA RANCA KALAPA, KABUPATEN TANGERANG MELALUI INOVASI PRODUK BORING’S - Abdul Rachman; Muhammad Fajar Ash Shidiqi; Sri Tamara Devy; Tresya meilina; Siti Nur Afifah; Widi Astuti; Silvi Octavani; Sari Wulandari; Vanny Nurhanifah; Muhammad Rizky Asrof; Ninis Meliyana Putri; Zahra Syafinatunnisa; Siti Nurmila Sari; Nila Hikma Karmelia (Jurnal Abdi Insani, 2022)
This activity aims to assist UMK entrepreneurs in Ranca Kalapa Village in increasing the selling value of Rengginang products which are traditional foods so that they can upgrade these products. The role of UMK entrepreneurs is very important in improving the regional economy and the country's economy, so they are obliged to make many innovations and creations for their products in order to be able to compete well in the national and international arena. The method used in this activity is PAR (Participatory Action Research), which is a method that is part of research (Research) involving various stakeholders (relevant parties) in terms of assessing the actions to be carried out so that better changes are formed. Through this method, we innovate Rengginang products, in the form of Re-Branding, Re-Packing and Re-Promoting, so that existing products can meet the current market segment. The result of this activity is to produce a new product from rengginang innovation, namely Boring's (Bola Rengginang) served with chocolate wrap which can be a contemporary snack typical of Ranca Kalapa Village.